PENGEMBANGAN MODEL PEMBELAJARAN BAHASA ARAB BERBASIS TEORI KONSTRUKTIVISME DI PERGURUAN TINGGI - Nasution, Sahkholid; Zulheddi, Zulheddi (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This study aimed to: 1) describe the conditions of Arabic learning in the State Islamic university of North Sumatra (UIN SU) Medan; 2) develop the Arabic language learning model based on constructivism theory; and 3) know the level of validation of the Arabic language learning model based on constructivism theory. This research applied Research and Development (R & D) method with Four Ds model consisting of: define, design, development and dissemination. The results showed (1) the Arabic learning at UIN SU Medan needed much improvement because 48.32% of Arabic language lecturers still used a learning approach not encouraging students to learn actively, collaboratively, and confidently. In other words, the learning process was still teacher-centered. (2) The product (Arabic Language Learning Model) produced was an Arabic learning tool characterized by constructivism, which includes: Syllabus, RPS and Assessment. (3) Constructivism learning and Arabic learning experts assessed the products with an average value of 3.37 (very good).